Strategi Adaptasi Pemasaran Digital Produk Olahan Peternakan di Era Industri 4.0: Sebuah Tinjauan Literatur Sistematis (Systematic Literature Review) - Rais Mughni Salam; Asep Saeppani; Fadhil Irfan (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2026)
Digital transformation in the era of Industry 4.0 has forced the livestock sector, particularly processed product SMEs (UMKM), to adapt their marketing strategies. Conventional marketing methods are increasingly limited by geographical boundaries and high operational costs. This study aims to identify and analyze the most effective digital marketing adaptation strategies for processed livestock products using a Systematic Literature Review (SLR) approach. Data were collected from Google Scholar (2020–2025) using the PRISMA method. The results indicate that the most dominant strategies are the utilization of Social Commerce (TikTok & Instagram) for brand awareness and Marketplaces (Shopee/Tokopedia) for transaction efficiency. Furthermore, successful adaptation requires a transition from